Design Of A Mathematics Test Instrument Based On Pharmacy Vocational Training With Rasch Model Analysis On Students' Mathematical Problem-Solving Ability - Hary Nurprio Utomo; Muhtarom Muhtarom; Ida Dwijayanti (Universitas Wiralodra, 2025)
This research aims to measure students' mathematical problem-solving abilities using a pharmacy-based vocational mathematics test instrument with Rasch model analysis. The development model in this research is 4D design by Thiagarajan, which includes the stages: define, design, development, and disseminate, but in this study, it is limited to the Development stage. Respondent data from 30 students with a total of 5 questions yielded results indicating that the expert validity of all five questions is very good. The reliability of test items and students was analyzed, revealing weak reliability for students and sufficient reliability for the questions; and the reliability of the interaction between individuals or students with the overall test items falls into the weak category. The overall difficulty level of the questions falls into the fairly good category, which includes items that are neither too difficult nor too easy, specifically in the moderate, easy, and difficult categories. In conclusion, the analysis of the pharmacy vocational-based mathematics test instrument using the Rasch model analysis is declared valid, reliable, and has a good level of difficulty.